2006
DOI: 10.1021/jp062105f
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Flowerlike AlOOH (Boehmite) 3D Nanoarchitectures

Abstract: In this work, a hydrothermal route using an ethanol-water solution to progressively synthesize a sequence of flowerlike three-dimensional gamma-AlOOH boehmite nanostructures without employing templates or matrixes for self-assembly is presented. The flowerlike boehmite nanoarchitectures exhibit three hierarchies of self-organization, i.e., single-crystalline nanorods, nanostrips, and bundles, which are characterized by scanning and transmission electron microscopy. The sequence of products obtained after diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 39 publications
5
76
1
Order By: Relevance
“…Therefore, a plausible growth mechanism is proposed based on the above results. In the initial stage, the anhydrate AlCl 3 is hydrolyzed in the mixture solvent to form amorphous Al(OH) 3 colloids, which is similar to the previous report [16]. Then the Al(OH) 3 colloids are transformed into AlOOH nanoparticles at elevated temperature in the hydrothermal surroundings.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, a plausible growth mechanism is proposed based on the above results. In the initial stage, the anhydrate AlCl 3 is hydrolyzed in the mixture solvent to form amorphous Al(OH) 3 colloids, which is similar to the previous report [16]. Then the Al(OH) 3 colloids are transformed into AlOOH nanoparticles at elevated temperature in the hydrothermal surroundings.…”
Section: Methodssupporting
confidence: 65%
“…Therefore, boehmite with various morphologies and sizes has attracted considerable interest in the past few years. So far, boehmite with different morphologies, such as nanotubes [11,12], nanobelts [13], nanofibers [14,15], flower-like [16] and cantaloupe-like [17] nanostructures, have been synthesized through various methods. However, to the best of our knowledge, the synthesis of uniform 3D γ-AlOOH architectures via DMSO-H 2 O system has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of nanomaterials with well-controlled morphology and size is a key issue in current nano-science research because they are key parameters to determine the optical, electronic, magnetic, and chemical properties [1][2][3][4][5][6][7]. In particular, to synthesize complex three-dimensional (3D) architectures in nanometer or micrometer is desirable for advanced functional nanomaterials via a self-assembly process [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Also, flowerlike three-dimensional nanoarchitecture of boehmite have been observed by Zhang et al [41]. Other authors had found nanosheets when their preparation of boehmite samples reached a pH near 7 [42] and also plate-shaped particles when their preparation was made with NaOH at pH of 7 [18].…”
Section: Semmentioning
confidence: 72%